2010
DOI: 10.1111/j.1440-1797.2010.01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis practice in Australia and New Zealand: A call to action

Abstract: Peritoneal dialysis technique survival in Australia and New Zealand is lower than in other parts of the world. More than two-thirds of technique failures are related to infective complications (predominantly peritonitis) and 'social reasons'. Practice patterns vary widely and more than one-third of peritoneal dialysis units do not meet the International Society of Peritoneal Dialysis minimum accepted peritonitis rate. In many cases, poor peritonitis outcomes reflect significant deviations from international gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 75 publications
3
83
0
1
Order By: Relevance
“…Indeed, the proportion of patients planning to start HD at the time of randomization who subsequently changed their minds and started on PD instead was only 5% in both the early-start and latestart groups (p = 0.76). Although previous studies have reported that 30% -50% of end-stage renal failure patients who receive pre-dialysis education will choose PD (36)(37)(38), only a fraction of such patients will actually start on PD (39,40). Those results suggest that greater effort may be required to fully support and resource a patient's decision to undertake PD, particularly during Prn-yrs = person-years; HR = hazard ratio; CI = confidence interval; CV = cardiovascular; MI = myocardial infarction.…”
Section: Pdimentioning
confidence: 99%
“…Indeed, the proportion of patients planning to start HD at the time of randomization who subsequently changed their minds and started on PD instead was only 5% in both the early-start and latestart groups (p = 0.76). Although previous studies have reported that 30% -50% of end-stage renal failure patients who receive pre-dialysis education will choose PD (36)(37)(38), only a fraction of such patients will actually start on PD (39,40). Those results suggest that greater effort may be required to fully support and resource a patient's decision to undertake PD, particularly during Prn-yrs = person-years; HR = hazard ratio; CI = confidence interval; CV = cardiovascular; MI = myocardial infarction.…”
Section: Pdimentioning
confidence: 99%
“…Despite the existence of best-practice guidelines, concerns have been raised that these recommendations are not followed by practitioners (11,12,21,22,25). Furthermore, deviation from recommendations may be an underappreciated contributor to PD technique failure (11,12,21,22).…”
Section: Patient Education and Care For Pd Catheter Placementmentioning
confidence: 99%
“…Furthermore, deviation from recommendations may be an underappreciated contributor to PD technique failure (11,12,21,22).…”
Section: Patient Education and Care For Pd Catheter Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…eritonitis is a frequent, major complication of per i toneal dialysis (PD) that often results in consid erable morbidity, technique failure and mortality (1)(2)(3). These adverse clinical outcomes are more common in gram-negative PD-associated peritonitis (4,5).…”
mentioning
confidence: 99%